Light Control-Induced Oxygen Vacancy Generation and In Situ Surface Heterojunction Reconstruction for Boosting CO2 Reduction - Zhimin Yuan; Xianglin Zhu; Qichao Gao; Zaiyong Jiang (Molecules, 2023)
The weak adsorption of CO2 and the fast recombination of photogenerated charges harshly restrain the photocatalytic CO2 reduction efficiency. The simultaneous catalyst design with strong CO2 capture ability and fast charge separation efficiency is challenging. Herein, taking advantage of the metastable characteristic of oxygen vacancy, amorphous defect Bi2O2CO3 (named BOvC) was built on the surface of defect-rich BiOBr (named BOvB) through an in situ surface reconstruction progress, in which the CO32− in solution reacted with the generated Bi(3−x)+ around the oxygen vacancies. The in situ formed BOvC is tightly in contact with the BOvB and can prevent the further destruction of the oxygen vacancy sites essential for CO2 adsorption and visible light utilization. Additionally, the superficial BOvC associated with the internal BOvB forms a typical heterojunction promoting the interface carriers’ separation. Finally, the in situ formation of BOvC boosted the BOvB and showed better activity in the photocatalytic reduction of CO2 into CO (three times compared to that of pristine BiOBr). This work provides a comprehensive solution for governing defects chemistry and heterojunction design, as well as gives an in-depth understanding of the function of vacancies in CO2 reduction.